STUDY OF COORDINATION OF PROTECTION SYSTEMS ON LA 3 FEEDERS USING OVER CURRENT RELAY (OCR) AT PT PL RAYON, LANGSA CITY - Dipo Rizky Amrullah; Subhan; Rudi Syahputra (Bulletin of Engineering Science, Technology and Industry, 2023)
relay that works based on an increase in current that exceeds a certain safety value and a certain period of time. The main function of this overcurrent relay is to sense the presence of overcurrent and then give the command to the circuit breaker (PMT) to open. The working principle of the Over Current Relay (OCR) is a relay that works against excess current, it will work if the flowing current exceeds the setting value (Iset) or protection that works due to a short circuit between the phases. Basically, an overcurrent relay is a device that detects the amount of current flowing through a network with the help of a current transformer. The price or amount that is allowed to pass is called the setting.